THE TAUHID FLAG: The Value, Meaning and Philosophy - Jayadi, Rahmat (AKADEMIK: Jurnal Mahasiswa Humanis, 2023)
More than 80 percent of Indonesia's population adheres to Islam, also known as Muslims. However, Indonesia is a republic with the principle of unity consisting of many tribes, religions and ethnicities, hence it is also known as Bhineka Tunggal Ika. Therefore, Islam in Indonesia has its own color, with various points of view. This research was conducted to find out the views of the Indonesian people towards Islamic symbols, in this case the Tauhid flag. Scientifically, this research uses a qualitative approach with literature review as its research method. Guidelines for discussing research refer to Pierce's views, regarding the study of symbols. The object of this research is the Tauhid flag with descriptive analysis techniques. The results of the study suggest that, philosophically, not all flags bearing the word Tauhid are said to be monotheistic flags. A flag is said to be a Tauhid flag, if the flag officially becomes a symbol of an Islamic government. In addition, the Tauhid flag has value and meaning as an effort to struggle for the Religion of Allah, not based on power.